Zebrafish Adar2 Edits the Q/R site of AMPA receptor Subunit gria2α transcript to ensure normal development of nervous system and cranial neural crest cells. - I-Chen Li (Public Library of Science (PLoS), 2014)
Background Adar2 deaminates selective adenosines to inosines (A-to-I RNA editing) in the double-stranded region of nuclear transcripts. Although the functions of mouse Adar2 and its biologically most important substrate gria2, encoding the GluA2 subunit of AMPA (α-amino-3-hydroxy-5-methyl-4-isoxazole propionic acid) receptor, have been extensively studied, the substrates and functions of zebrafish Adar2 remain elusive. Methods/principal findings Expression of Adar2 was perturbed in the adar2 morphant (adar2MO), generated by antisense morpholio oligonucleotides. The Q/R editing of gria2α was reduced in the adar2MO and was enhanced by overexpression of Adar2, demonstrating an evolutionarily conserved activity between zebrafish and mammalian Adar2 in editing the Q/R site of gria2. To delineate the role of Q/R editing of gria2α in the developmental defects observed in the adar2MO, the Q/R editing of gria2α was specifically perturbed in the gria2αQRMO, generated by a morpholio oligonucleotide complementary to the exon complementary sequence (ECS) required for the Q/R editing. Analogous to the adar2-deficient and Q/R-editing deficient mice displaying identical neurological defects, the gria2αQRMO and adar2MO displayed identical developmental defects in the nervous system and cranial cartilages. Knockdown p53 abolished apoptosis and partially suppressed the loss of spinal cord motor neurons in these morphants. However, reducing p53 activity neither replenished the brain neuronal populations nor rescued the developmental defects. The expressions of crestin and sox9b in the neural crest cells were reduced in the adar2MO and gria2αQRMO. Overexpressing the edited GluA2αR in the adar2MO restored normal expressions of cresting and sox9b. Moreover, overexpressing the unedited GluA2αQ in the wild type embryos resulted in reduction of crestin and sox9b expressions. These results argue that an elevated GluA2αQ level is sufficient for generating the cranial neural crest defects observed in the adar2MO. Our results present a link between dysfunction of AMPA receptors and defective development of the nervous system and cranial neural crest in the zebrafish.